Employer Branding and Person-Organization Fit in Building Career Intention Gen Z - Imam Abrori; Via Lailatur Rizki; Rezha Isyraqi Qastalano; Rizky Adhitya Nugroho (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the effect of Employer Branding and Person-Organization Fit on Career Intention of Digital Business Study Program students at Jember State Polytechnic. This research uses a quantitative approach with an explanatory method. The research sample amounted to 72 students selected through purposive sampling technique. Data were collected through a closed questionnaire and analyzed using multiple linear regression. The results showed that simultaneously, Employer Branding and Person-Organization Fit had a significant effect on Career Intention (p < 0.05), but partially only Person-Organization Fit had a significant effect. The Person-Organization Fit variable has a dominant influence, while Employer Branding does not show a significant influence individually. In conclusion, value fit between individuals and organizations is a key factor in shaping students' career intentions.